Gephi cookbook : over 90 hands-on recipes to master the art of network analysis and visualization with Gephi - Khokhar, Devangana (Quick answers to common problems, 2015)
If you want to learn network analysis and visualization along with graph concepts from scratch, then this book is for you. This is ideal for those of you with little or no understanding of Gephi and this domain, but will also be beneficial for those interested in expanding their knowledge and experience.